Study on Engine Learning Experiencing Low Power On Cummins QSL 9.3L Engine - Raihan Trinanda Agsya; Rahman Filzi; Rahmat Noval; Hong Yue (MBI, 2024)
The Cummins QSL 9.3L diesel engine is a production engine from CLG or Cummins Liugong. This type of engine is typically used in heavy equipment such as Wheel Loaders. A diesel engine is an internal combustion engine where the combustion process occurs inside the engine itself, and pure air is compressed within the combustion chamber, resulting in high air pressure. It operates in four strokes. This engine experienced low power, causing it to malfunction, which led to abnormal operation. Various checks were conducted, including inspection of diesel fuel, fuel tank inspection, engine oil level check, visual inspection of the air cleaner, water separator check, Fuel Feed Pump check, and Clearance Valve Lash check. The problem identified was the mismatch of Valve Lash clearance in the engine, resulting in low power. The repair step involved adjusting the Valve lash using a Feeler Gauge. The purpose of this research is to provide an explanation of troubleshooting and to perform repairs on engines experiencing low power